Relasi Bahasa dan Hermeneutik dalam Prses Pemaknaan Teks - Muhammad Nur Haris Asyrofi; Nurul Fahmi (STAI Hidayatut Thullab Kediri, 2025)
This research stems frm the cmplexity f interpreting religius texts, which are ften cnfined t literal understandings despite language pssessing symblic dimensins that shape human reality. The primary prblem addressed is hw the relatinship between language and hermeneutics functins t reveal dynamic textual meanings. Within Islamic studies discurse, this study psitins hermeneutics nt merely as a linguistic tl, but as a methdlgical bridge cnnecting the text, the reader, and the sci-histrical cntext. The discussin is cnducted by analyzing three aspects: the nature f language as a medium f revelatin, the functin f hermeneutics as a methd fr interpreting implicit meanings, and the reciprcal synthesis between the tw. The results indicate that the intercnnectin between language and hermeneutics is capable f reslving semantic ambiguity and ensuring the relevance f classical texts in the mdern era. This synergy allws texts t be understd critically and cntextually withut lsing their authenticity. These ideas are cmprehensively summarized in this article, titled